Screening fertilizers for their phosphorus runoff risk using laboratory methods. Issue 4 (29th May 2021) - da Silva, Rodrigo C.; Degryse, Fien; Baird, Roslyn; Mallarino, Antonio P.; McLaughlin, Michael J.
Abstract: Losses of phosphorus (P) from fertilized fields may result in degradation of water quality. Various initiatives are under evaluation to minimize water contamination, including the adoption of less soluble or coated P fertilizer formulations aiming to mitigate losses of P in runoff. Field‐based rainfall simulators are traditionally used to evaluate P runoff, but using these is time consuming, labor intensive, and costly given the complex apparatus and analyses involved. We hypothesized that laboratory‐based methods could be useful to evaluate the risk of P runoff from fertilizers. In order to identify a rapid, inexpensive, and efficient screening process, we compared two laboratory‐scale measurements, one in water (based on electrical conductivity measurements) and one in soil (based on visualization of P diffusion in soil), with runoff results from field‐, glasshouse‐, and laboratory‐based rainfall simulators, using coated soluble phosphate fertilizers. The laboratory‐based methods assessing the P release rate in water and in soil correlated closely ( r ≥ .96) with the losses of P obtained in the three rainfall simulators regardless of the type of coating or solubility of the fertilizer. The faster and inexpensive electrical conductivity and diffusion visualization methodologies were useful to rank the fertilizers by P release to runoff. Hence, these tools may be useful for screening fertilizer formulations with respect to their runoff risk. Core Ideas: Phosphorus release in water from fertilizers correlated well with the diffusion rate in soil. Results from laboratory dissolution assays and rain simulators are strongly correlated. Low‐cost laboratory assays allow ranking fertilizers in terms of their runoff risk.